Morphology of immature stages of Paraegidium costalimai (Coleoptera: Scarabaeidae: Orphninae) and remarks on egg-busters in Scarabaeidae first‑instar larvae - Sousa, Rafael Clayton de Jesus e; Fuhrmann, Juares (Papéis Avulsos de Zoologia, 2020)
Studies about the immature stages of Orphninae (Coleoptera: Scarabaeidae) species are scarce. The subfamily includes 214 species, but only 5 have the immature stages described: Chaetonyx robustus liguricus Mariani, 1946, Hybalus benoiti Tournier, 1864, H. rotroui Petrovitz, 1964 and Triodontus nitidulus (Guérin, 1844) from Old World; and Aegidium cribratum Bates, 1887 from the New World. The Neotropical genus Paraegidium Vulcano, Pereira & Martinez, 1966 encompass five species, mainly recorded from Brazil. Herein, the immature stages of P. costalimai Vulcano, Pereira & Martinez, 1966 are described and illustrated, along with remarks on the presence of egg-buster in Scarabaeidae first-instar larvae. A key to the third-instar larvae of known Orphninae and a comparative study of chaetotaxy are also provided.